2016
DOI: 10.1371/journal.pone.0168552
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of CC16 in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating disease of unknown etiology. The pathogenic mechanisms are unclear, but evidence indicates that aberrantly activated alveolar epithelial cells secrete a variety of mediators which induce the migration, proliferation and activation of fibroblasts and finally the excessive accumulation of extracellular matrix with the consequent destruction of the lung parenchyma. CC16 (approved symbol SCGB1A1), a putative anti-inflammatory protein produced by “club” cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…BAL pellets from patients diagnosed with IPF or hypersensitivity pneumonitis [ 30 ], diagnosed according to published consensus statements were received as 1 ml frozen pellets. The local ethics committee of the Instituto Nacional de Enfremedades Respiratorias (INER, Mexico City, Mexico) approved the human BAL study.…”
Section: Methodsmentioning
confidence: 99%
“…BAL pellets from patients diagnosed with IPF or hypersensitivity pneumonitis [ 30 ], diagnosed according to published consensus statements were received as 1 ml frozen pellets. The local ethics committee of the Instituto Nacional de Enfremedades Respiratorias (INER, Mexico City, Mexico) approved the human BAL study.…”
Section: Methodsmentioning
confidence: 99%
“…Further, other studies have observed an expansion of KRT5 + cells into the alveolar parenchyma of bleomycin-injured or influenza-infected mouse lungs (12,13), with one study suggesting that these cells may be distinct from airway basal and club cells (12). Consistently, several studies have reported an expansion of KRT5 + and SCGB1A1 + epithelial cells in fibrotic IPF lungs (14)(15)(16); however, the role of these epithelial cells in the relentless and progressive lung remodeling observed in this disease remains elusive.…”
Section: Introductionmentioning
confidence: 71%
“…As our model system contains rare individual KRT5 + basal‐like cells, their role in the IPF‐RC mediated effects cannot be excluded. However, as IPF‐RC treatment of small airway basal cells induced a strong upregulation of MUC5AC , but not MUC5B , contrary to the abundant emergence of aberrant MUC5B + cells in the bronchiolized distal airspaces in IPF patients, as well as suppressed the expression of transcripts upregulated in the IPF lung such as SCGB1A1 and FOXJ1, the airway‐like phenotype observed in iPSC‐derived IPF‐RC cultures is unlikely the sole result of basal‐like cell expansion and differentiation 5,6,76,77 . Moreover, IPF‐RC stimulation did not induce proliferation of primary small airway basal cells compared to controls.…”
Section: Discussionmentioning
confidence: 96%